Relative Age Effect of Sport Academy Adolescents, a Physiological Evaluation - Staffan Ek; Per Wollmer; Magnus K. Karlsson; Tomas Peterson; Ola Thorsson; M. Charlotte Olsson; Julia S. Malmborg; Magnus Dencker (MDPI AG, 2020)
The relationship between birth quarter distribution and physiological characteristics related to athletic skills, in adolescent sport academy students has not been fully investigated. In a cross-sectional study, we recruited 86 boys and 52 girls aged 12−14 years during their first term at a sport academy school. We measured body size, cardiac size, pulmonary function, body composition, lower body power, cardiorespiratory fitness parameters, and running endurance by standard methods and analyzed these estimates in relation to birth quarter by ANOVA. Birth quarter distribution in our cohort was compared with birth quarter distribution in the same ages in the whole of Sweden and analyzed by logistic regression. The academy had an overrepresentation of students born in the first quartile of the year compared to those born in the last quartile (odds ratio 2.3 (95% CI: 1.1−4.7)). When comparing the physiological characteristics between birth quarters, uniformity is prominent since out of 26 performed physiological and anthropometric tests only four showed statistically significant group differences. We thus believe that the selection process to the sport academy favours athletes with higher chronological age, i.e., a so-called relative age effect is present.